The interplay between mothers’ and children behavioral and psychological factors during COVID-19: an Italian study - Di Giorgio, Elisa; Di Riso, Daniela; Mioni, Giovanna; Cellini, Nicola (European child & adolescent psychiatry, 2021)
Italy has been the first nation outside of Asia to face the COVID-19 outbreak. To limit viral transmission of infection, by March 10th, 2020, the Italian Government has ordered a national lockdown, which established home confinement, home ( smart ) working, and temporary closure of non-essential businesses and schools. The present study investigated how these restrictive measures impacted mothers and their pre-school children’s behavioral habits (i.e., sleep timing and quality, subjective time experience) and psychological well-being (i.e., emotion regulation, self-regulation capacity). An online survey was administered to 245 mothers with pre-school children (from 2 to 5 years). Mothers were asked to fill the survey thinking both on their habits, behaviors, and emotions and on those of their children during the quarantine, and retrospectively, before the national lockdown (i.e., in late February). A general worsening of sleep quality and distortion of time experience in both mothers and children, as well as increasing emotional symptoms and self-regulation difficulties in children, was observed. Moreover, even when the interplay between the behavioral and psychological factors was investigated, the factor that seems to mostly impact both mothers' and children's psychological well-being was their sleep quality. Overall, central institutions urgently need to implementing special programs for families, including not only psychological support to sustain families with working parents and ameliorating children's management.